PRINCIPLE OF CONTINUITY IN TEACHING RUSSIAN AND WORLD LITERATURE: BACHELOR, MASTER - Sayfullayev Jahongir; Axmedjanova Dilraboxon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: In the context of credit-modular education in a higher educational institution, the principle of continuity in the concept of teaching Russian and world literature in the undergraduate direction ("Philology and teaching languages (Russian language)" and "Russian language in foreign language groups"), which is being built on a combination of traditional (explanatory and illustrative, reproductive, heuristic, research) methods and innovative (systemic, “learning a language by reading the classics”, “MKhAT”) approaches, as well as taking into account such phenomena as globalization, the dialogue of cultures. This, in turn, ensures continuity in obtaining an academic degree in the Master's specialty "Literary Studies (Russian Literature)" and "Russian Language and Literature in the Space of World Culture". As a result, a methodology is developed that is necessary for conducting research activities